2020
DOI: 10.1021/acs.orglett.0c01348
|View full text |Cite
|
Sign up to set email alerts
|

Step-Economic Synthesis of Biomimetic β-Ketopolyene Thioesters and Demonstration of Their Usefulness in Enzymatic Biosynthesis Studies

Abstract: Studies on the biosynthetic processing of polyene thioester intermediates are complicated by limited access to appropriate substrate surrogates. We present a step-economic synthetic access to biomimetic β-ketopolyene thioesters that is based on an Ir-catalyzed reductive Horner−Wadsworth−Emmons olefination. New β-ketotriene and pentaenethioates of pantetheine and N-acetylcysteamine were exemplarily synthesized via short and concise routes. The usefulness of these compounds was demonstrated in an in vitro assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In order to probe the selectivity of the BfL1 hydrolase we synthesised SNAC, pantetheine, CoA and ACP-bound potential substrates (Scheme 2). 22,23 In our previous work we assumed that the acyl group should be unsaturated (e.g. an E-hex-2-enoyl substrate) but this was unproven, 10 so we made both E-hex-2enoyl 14a-d and hexanoyl 15a-d substrates.…”
Section: Hydrolasementioning
confidence: 99%
“…In order to probe the selectivity of the BfL1 hydrolase we synthesised SNAC, pantetheine, CoA and ACP-bound potential substrates (Scheme 2). 22,23 In our previous work we assumed that the acyl group should be unsaturated (e.g. an E-hex-2-enoyl substrate) but this was unproven, 10 so we made both E-hex-2enoyl 14a-d and hexanoyl 15a-d substrates.…”
Section: Hydrolasementioning
confidence: 99%
“…The stereoselectivity of isolated KRs is reproduced in vitro if the structure of the acyl part of SNAC thioesters matches that of the biosynthetic precursor but can be entirely altered in response to minimal structural changes. [20][21][22][23]27 Several studies, for example, showed that TylKR1 from the first elongation module of the tylactone-forming PKS reduces the racemic pentane thioate 21 to the expected 2-D,3-D-configured product (B1type reduction) by si face hydride addition to 2-D-21 that is continuously formed by spontaneous C-2 racemization. In contrast, a 2-L,3-L-configured main product (A2-type) was obtained with butanethioate 20, resulting from the re face reduction of 2-L-20.…”
mentioning
confidence: 99%
“…21−23 In the case of MycKRB from the mycolactone PKS, the expected B-type selectivity was observed with polyene 29, mimicking polyunsaturated precursors like 50, and not with 21. 19,27 The structure of the polyketide chain thus has a relevant influence on the stereoselectivity of KR domains, making structure−function relationships crucial for a better understanding of natural PKS and for successful PKS engineering.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] On the other hand, PKS domains frequently show relaxed substrate specicity and, particularly in the case of domains that catalyse synthetically attractive reactions, an application in chemoenzymatic synthesis is thus conceivable. 6,[8][9][10][11][12][13] Various recent reports have highlighted the existing potential of PKS enzymes for this purpose. [14][15][16][17][18][19] Immobilisation is an effective way to increase the practical value of enzymes by providing them with higher stability and recyclability.…”
mentioning
confidence: 99%